RECONSTRUCTING CONTRACT LAW: CHALLENGES AND WEAKNESSES IN PROTECTING CONSUMER RIGHTS AND ECONOMIC JUSTICE IN THE DIGITAL ERA - Teuku Yudi Afrizal; Nasrianti; Sofyan Jafar; Muhibuddin; Zulkifli (PT. Radja Intercontinental Publishing, 2025)
The rapid expansion of digital platforms in Indonesia has transformed the country's economy, creating significant opportunities for businesses and consumers alike. According to the e-Conomy SEA 2023 report, e-commerce transactions in Indonesia reached IDR 487.01 trillion in 2024, marking it as one of the largest digital markets in Southeast Asia (Google, Temasek, & Bain, 2023). However, despite the economic growth, the dominance of these platforms has introduced structural inequalities that disadvantage consumers, particularly in terms of data privacy, misleading advertisements, and lack of transparency in pricing and contract terms. Traditional contract law offers a critical perspective on these issues, grounded in principles of justice, honesty, and the prohibition of uncertainty. These principles are essential for addressing the challenges arising from digital transactions, where platform monopolies and the exploitation of consumer data have become widespread. However, current Indonesian contract law, including Law No. 8 of 1999 on Consumer Protection and Law No. 27 of 2022 on Personal Data Protection, has failed to adequately protect consumers in the digital space, as these regulations were designed for traditional markets and have not evolved to address the complexities of platform-based digital contracts. This study uses a normative juridical approach to analyze the gaps in Indonesia’s current legal framework and examines how traditional principles can provide a foundation for improving consumer protection in the digital economy. By emphasizing distributive justice, platform accountability, and algorithmic transparency, the research proposes a legal reconstruction model for Indonesia that integrates human rights principles and global best practices. The findings suggest that legal reforms are urgently needed to ensure fairness, equitable access, and protection for digital consumers while fostering a more just and transparent digital marketplace.